The impact of public environmental concerns on port sustainability: evidence from 44 port cities in China - Jia Shen; Xiaohong Ren; Zhitao Feng; Jiayun Nie (Frontiers in Marine Science)
Port construction and operations significantly impact the surrounding environment, creating an urgent need to explore pathways for enhancing port sustainability. Public environmental concern plays a vital role in driving environmental governance and offers new directions for improving port sustainability. Using panel data from 44 coastal ports and their respective cities between 2010 and 2021, this study empirically analyzes the impact of public environmental concern on port sustainability and its underlying mechanisms. Additionally, we examine how this impact varies across different city samples. The baseline regression results demonstrate that public environmental concern has a significant positive impact on port sustainability. This finding remains robust after a series of robustness checks and addressing endogeneity issues. Mechanism analysis reveals that public environmental concern can enhance port sustainability by increasing local government environmental investments. Furthermore, the development of digital infrastructure can amplify the positive effect of public environmental concern on port sustainability. Heterogeneity analysis indicates that the positive impact of public environmental concern on port sustainability is stronger in cities with lower government environmental regulation intensity, lower pollution emissions, higher education levels, and greater transparency in environmental information disclosure.